THE CORRELATION BETWEEN DIAMETER OF ATRIAL SEPTAL DEFECT WITH THE MEAN PULMONARY ARTERY PRESSURE IN ADULT - , SAKIINAH BINTI HASAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Atrial septal defect is one of the most common congenital cardiac anomaly which are frequently diagnosed in adults also with the increasing in pulmonary hypertension in the patients. Hence, a research needs to be done to see whether atrial septal defect correlates with the mean pulmonary artery pressure. Objectives : The objective of this study is to find out the correlation between diameter of atrial septal defect and mean pulmonary artery pressure. Method : This was a retrospective study using the data from atrial septal defect registry. The survey was conducted in Department of Cardiology and Vascular Medicine FM UGM and Dr. Sardjito Hospital, Yogyakarta. The data analysis was done in December 2013 using IBM SPSS 20. Result : There is no significant correlation between diameter of atrial septal defect and the mean pulmonary artery pressure. Pearson correlation test shows weak and positive correlation (r = 0.127), however the correlation is not significant (p=0.204). Conclusion: On the basis of the result obtained in this study, it may be concluded that there is no statistically significant regarding the correlation between diameter atrial septal defect and mean pulmonary artery pressure.